2017
DOI: 10.19126/suje.307045
|View full text |Cite
|
Sign up to set email alerts
|

Yabancı Dil Olarak Türkçe Öğrenenlerin Okuma Kaygıları ve Okuduğunu Anlama Becerileri

Abstract: Öz. Bu araştırmanın amacı, yabancı dil olarak Türkçe öğrenenlerin okuma kaygıları ile okuduğunu anlama becerileri arasındaki ilişkiyi ortaya çıkarmaktır. Bu amaç doğrultusunda 510 yabancı dil olarak Türkçe öğrenen B düzeyinde öğrenci örneklem olarak alınmıştır. Çalışmada veri toplamak amacıyla yabancı dil olarak Türkçe öğrenen B düzeyindeki öğrencilere yönelik "Okuma Kaygısı Ölçeği" ve "Okuduğunu Anlama Başarı Testi" geliştirilmiştir. Öğrencilerin Okuduğunu Anlama Başarı Testi'nden elde ettikleri puanlar ile O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
23

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
1
9
0
23
Order By: Relevance
“…Many factors in teaching Turkish as a foreign language can cause foreign language anxiety. Altunkaya and Erdem (2016) (Altunkaya & Erdem, 2016), "Listening and reading" (Altunkaya, 2017), "Reading -writing" (Varışoğlu, 2016 ), "Reading anxiety and reading errors" (Atasoy & Temizkan, 2018), "Speaking anxiety" (Boylu & Çangal, 2015), (Tuncel, 2015), (Şen & Boylu, 2015), and "Foreign language anxiety" (İşcan, 2016), (Polatcan, 2018) are, at the first step, the studies on anxiety in teaching Turkish as a foreign language that attract attention. These studies provide guidance to teachers on how to teach Turkish lessons more efficiently and effectively.…”
Section: Results Of Foreign Language Anxietymentioning
confidence: 99%
“…Many factors in teaching Turkish as a foreign language can cause foreign language anxiety. Altunkaya and Erdem (2016) (Altunkaya & Erdem, 2016), "Listening and reading" (Altunkaya, 2017), "Reading -writing" (Varışoğlu, 2016 ), "Reading anxiety and reading errors" (Atasoy & Temizkan, 2018), "Speaking anxiety" (Boylu & Çangal, 2015), (Tuncel, 2015), (Şen & Boylu, 2015), and "Foreign language anxiety" (İşcan, 2016), (Polatcan, 2018) are, at the first step, the studies on anxiety in teaching Turkish as a foreign language that attract attention. These studies provide guidance to teachers on how to teach Turkish lessons more efficiently and effectively.…”
Section: Results Of Foreign Language Anxietymentioning
confidence: 99%
“…In the study of the relationship between comprehension and reading anxiety read by Altunkaya (2015), the researcher's reading attained a negative correlation between the scores obtained from the reading achievement test and the reading anxiety scale, resulting in a decrease in the achievement score from the reading comprehension test as the reading anxiety increased. This research has revealed similar results with the increase of vocabulary and decrease of reading anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zbornik (2001), reading anxiety is a special and situational fob involving physical and cognitive reactions to reading activity. Altunkaya (2015) states that this anxiety situation in the student can be eliminated by including activities that encourage and reduce anxiety during the educational activities. In the process of learning a foreign language, the mood and individual differences in the individual are among the factors influencing reading and listening from their understanding skills.…”
Section: Extended Abstract Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…
The aim of this study is to determine the reading anxiety levels of Turkish as a foreign language. The Reading Anxiety Scale of Reading Students was used as a foreign language teacher developed by Altunkaya and Erdem (2017) in order to determine the reading anxiety of students who learned Turkish as a foreign language. The study group consisted of 170 foreign students studying at Mehmet Akif Ersoy University, İnönü University and Mersin University Turkish Teaching Centers during the second semester of the academic year 2017-2018.
…”
mentioning
confidence: 99%